The Effect of Gracilaria verrucosa Seaweed Flour Proportion with White Glutinous Rice Flour (Oryza sativa Glutinosa) and CMC (Carboxy Methyl Cellulose) Concentration on Physical and Chemical Characteristics of Seaweed Dodol - Dieo Riezma Elfahira; Lukman Hudi; Syarifa Ramadhani Nurbaya (Procedia of Engineering and Life Science, 2022)
This study used a factorial randomized block design. The first factor is the proportion of Gracilaria verrucosa seaweed flour with white glutinous rice flour (P): (P1) 75%:25%, (P2) 50%:50%, and (P3)25%:75%, the second factor is concentration of CMC (K): (K1) 2%, (K2) 4%, and (K3) 6%. The data were analyzed using analysis of variance, followed by the BNJ test (Honest Significant Difference) at 5% level, and the organoleptic test was analyzed using the Friedman test. The best treatment was obtained in the P3K3 treatment (proportion of Gracilaria verrucosa seaweed flour with white glutinous rice flour 75%: 25% and CMC concentration 6%) with color L (lightness) 43.1; *a (redness) 4.9; *b (yellowness) 10.6; 1.66N texture; water content 37.40%; free fatty acid content of 0.28%; reducing sugar content 0.4%; and antioxidant activity 368.6 Î¼g/ml.